2017
DOI: 10.1177/1475725717716624
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Delivery Approaches to Teaching Abnormal Psychology: Investigating Student Perceptions and Learning Outcomes

Abstract: This study compares the academic performance and perceptions of 114 undergraduate students enrolled in an abnormal psychology course. Specifically, this study focuses on whether face-to-face (F2F) or blended modalities are associated with student learning outcomes. In this study, data analysis was based upon the examination of end-of-course grades, final exams, and an end-of-course survey. The data revealed that the same course presented in a F2F and a hybrid modality was associated with nearly identical learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Although in theory it may seem straightforward to establish equivalence between remote and face-to-face learning contexts, in practice, it can be challenging. Even when instructors are careful to align course materials and assignments across formats, students may still perceive differences in the delivery, assessment, and overall structure of the course as a function of modality (Goette et al, 2017). Garratt-Reed et al (2016) reported lower student retention in the online version of an Introductory Psychology unit, a finding which aligns with other studies reporting differences in student retention in face-to-face and online courses (Bawa, 2016; Van Doorn & Van Doorn, 2014).…”
Section: Differences Between Learning Online Versus Face-to-facementioning
confidence: 99%
“…Although in theory it may seem straightforward to establish equivalence between remote and face-to-face learning contexts, in practice, it can be challenging. Even when instructors are careful to align course materials and assignments across formats, students may still perceive differences in the delivery, assessment, and overall structure of the course as a function of modality (Goette et al, 2017). Garratt-Reed et al (2016) reported lower student retention in the online version of an Introductory Psychology unit, a finding which aligns with other studies reporting differences in student retention in face-to-face and online courses (Bawa, 2016; Van Doorn & Van Doorn, 2014).…”
Section: Differences Between Learning Online Versus Face-to-facementioning
confidence: 99%